Respostas

2014-02-17T15:48:42-03:00
S=24-t

12m:
12=24+2t
12-24=2t
-12=2t
t=-6

18m: 
18=24+2t
18-24=2t
-6=2t
t=-3

10m:
10=24+2t
10-24=2t
-14=2t
t=-7

-24m:
-24=24+2t
-24-24=2t
-48=2t
t=-24

-6m: 
-6=24+2t
-6-24=2t
-30=2t
t=-15

b- (s=24+2t)
s=24+2.120
s=24+240
s=264m
2014-02-17T15:51:09-03:00
Resposta

A

12 = 24 + 2t
24 + 2t = 12
2t = 12 - 24
2t = -12
t = -12/2
t = -6s

O movel não passa pelo  12

18 = 24 + 2t
2t = 18 - 24
t = -6/2
t = -3s

O movel não passa pelo  18

10 = 24 + 2t
2t = 10 - 24
t = -14/2
t = -7s

O movel não passa pelo  10

-24 = 24 + 2t
24 + 2t = -24
2t = -24 - 24
2t = -48
t = -48/2
t = -24s

O movel não passa pelo  -24

-6 = 24 + 2t
24 + 2t = -6
2t = -6 - 24
2t = -30
t = -30/2
t = -15s

O movel não passa pelo  -6

2

s = 24 + 2.120
s = 24 + 240
s = 264m